I have the following raw SQL query:
UPDATE mySock s1
LEFT JOIN mySock s2
ON s1.parentId = s2.id
SET
s1.status = 1
s1.mylevel = (s2.mylevel + 1),
s1.parentString = CONCAT(s2.parentString, ':' CONCT(s1.id as char))
WHERE
s1.zz = 0;
and in create in Symfony 3.2
public function updateParentNew($idParent)
{
return $this->createQueryBuilder('s1')
->update('MyBundle:Stock', 's1')
->leftJoin(''MyBundle:Stock', 's2', 'WITH', 's2.id = s1.parentId')
->set('s1.zz', 1)
->set('s1.leveltask', 's2.leveltask + 1')
->set('s1.parentString', '?par2_string')
->where('s1.zz = 0')
->andWhere('s1.parentId = ?par1')
->setParameter('par1', $idParent)
->setParameter('par2_string', s2.parentString + ':' + (string)s1.id)
->getQuery()
->getSingleScalarResult();
}
It doesn't work. What is the way to Concat values (string and number)?
I would try something like this:
public function updateParentNew($idParent)
{
$qb = $this->createQueryBuilder('s1')
->update('MyBundle:Stock', 's1')
->leftJoin('MyBundle:Stock', 's2', 'WITH', 's2.id = s1.parentId')
;
$qb->set('s1.zz', 1)
->set('s1.leveltask', $qb->expr()->sum('s2.leveltask', 1))
->set('s1.parentString',
$qb->expr()->concat(
$qb->expr()->literal('s2.parentString'),
$qb->expr()->concat(':', $qb->expr()->literal('s1.id'))
))
->where('s1.zz = 0')
->andWhere('s1.parentId = :par1')
->setParameter('par1', $idParent)
->getQuery()
->getSingleScalarResult()
;
return $qb;
}
Related
class Main {
public static void main(String[] args) {
int n = 5, firstTerm = 0, secondTerm = 1;
System.out.println("Fibonacci Series till " + n + " terms:");
for (int i = 1; i <= n; ++i) {
System.out.print(firstTerm + " ");
// compute the next term
int nextTerm = firstTerm + secondTerm;
firstTerm = secondTerm;
secondTerm = nextTerm;
}
}
}
//Q) Unable to understand why firstTerm = secondTerm;
secondTerm = nextTerm; statement is written, can anyone explain me this concept
The fibonnaci sequence is defined by
F(0) = 0 // This is our first term
F(1) = 1 // This is the second term
F(n) = F(n - 1) + F(n - 2)
To calculate a term that is neither the first term, nor the second term, we need to sum, the two previous terms.
This is the reason why while iterating, the second term value is assigned to the first term and so on
You will have more details here
Does someone know such function that merges list of records
if all values to merge are records - merge them recursively
if all values to merge are arrays - concatenate arrays
If values can't be merged - the latter value is preferred
Example 1:
recursiveMergeAttrs [
{ a = "x"; c = "m"; list = [1]; }
{ a = "y"; b = "z"; list = [2]; }
]
returns
{ a = "y"; b = "z"; c="m"; list = [1 2] }
Example 2
recursiveMergeAttrs [
{
boot.loader.grub.enable = true;
boot.loader.grub.device = "/dev/hda";
}
{
boot.loader.grub.device = "";
}
]
returns
{
boot.loader.grub.enable = true;
boot.loader.grub.device = "";
}
P.S.
recursiveUpdate is not working
recursiveMergeAttrs = listOfAttrsets: lib.fold (attrset: acc: lib.recursiveUpdate attrset acc) {} listOfAttrsets
recursiveMergeAttrs [ { a = "x"; c = "m"; list = [1]; } { a = "y"; b = "z"; list = [2]; } ]
returns
{ a = "y"; b = "z"; c = "m"; list = [ 2 ]; }
Did it
{ lib, ... }:
with lib;
/*
Merges list of records, concatenates arrays, if two values can't be merged - the latter is preferred
Example 1:
recursiveMerge [
{ a = "x"; c = "m"; list = [1]; }
{ a = "y"; b = "z"; list = [2]; }
]
returns
{ a = "y"; b = "z"; c="m"; list = [1 2] }
Example 2:
recursiveMerge [
{
a.a = [1];
a.b = 1;
a.c = [1 1];
boot.loader.grub.enable = true;
boot.loader.grub.device = "/dev/hda";
}
{
a.a = [2];
a.b = 2;
a.c = [1 2];
boot.loader.grub.device = "";
}
]
returns
{
a = {
a = [ 1 2 ];
b = 2;
c = [ 1 2 ];
};
boot = {
loader = {
grub = {
device = "";
enable = true;
};
};
};
}
*/
let
recursiveMerge = attrList:
let f = attrPath:
zipAttrsWith (n: values:
if tail values == []
then head values
else if all isList values
then unique (concatLists values)
else if all isAttrs values
then f (attrPath ++ [n]) values
else last values
);
in f [] attrList;
in
recursiveMerge
Is there any possible way to make a linked list in cypher within one transaction ?
Iv'e tried ForEach with Match but according to neo4jClien it is not possible to set Match in ForEach.
My approach :
public static void save(List<Post> nodes)
{
var gclient = graphdb.getConnection();
var create1 = gclient.Cypher.Create("(p:Post {nodes})");
var match = gclient.Cypher.Match("((t)-[r:lastPost]->(last))");
var create3 = gclient.Cypher.Create("t-[:lastPost]->p, p-[:next]->last");
var delete = gclient.Cypher.Delete("r");
string query = create1.Query.QueryText + " " + match.Query.QueryText + " "
+ create3.Query.QueryText + " " + delete.Query.QueryText;
gclient.Cypher
.Match("(t:Tmp)")
.WithParam("nodes", nodes)
.ForEach("(newPost in {nodes} | " + query + ")")
.ExecuteWithoutResults();
}
Thanks in advance .
this should do the trick.
static Neo4jClient.Cypher.ICypherFluentQuery addnode<T>(Neo4jClient.Cypher.ICypherFluentQuery q, IList<T> items, int idx, string label)
{
string sq = string.Format("({0}:{1} {{{2}}})", "c" + idx, label, "a" + idx);
q = q.Create(sq).WithParam("a" + idx, items[idx]);
return q;
}
static Neo4jClient.Cypher.ICypherFluentQuery addlink<T>(Neo4jClient.Cypher.ICypherFluentQuery q, int idx1, int idx2)
{
string sq = string.Format("{0}-[:LINKEDTO]->{1}", "c" + idx1, "c" + idx2);
q = q.Create(sq);
return q;
}
public static void Sample<T>(List<T> items, GraphClient client)
{
Neo4jClient.Cypher.ICypherFluentQuery q = client.Connection.Cypher;
for (int i = 1; i < items.Count; i++)
{
q = addnode<T>(q, items, i-1, "MYITEM");
if(i>1)
q = addlink<T>(q, i-2, i-1);
}
q.ExecuteWithoutResults();
}
I'm struggling with this problem:
Given 2 strings:
s1 = '/foo/:bar/oof/:rab'
s2 = '/foo/lua/oof/rocks'
I would like to produce the following information:
If they match (these two above should match, s2 follows a pattern described in s1).
A table holding the values of s2 in with the corresponding name in s1. In this case we would have: { bar = "lua", rab = "rocks" }
I think this algorithm solves it, but I can't figure how to implement it (probably with gmatch):
store the placeholders : indexes as KEYS of a table, and the respective VALUES being the name of these placeholders.
Example with s1:
local aux1 = { "6" = "bar", "15" = "rab" }
With the keys of aux1 fetched as indexes, extract the values of s2
into another table:
local aux2 = {"6" = "lua", "15" = "rocks"}
Finally merge them two into one table (this one is easy :P)
{ bar = "lua", rab = "rocks" }
Something like this maybe:
function comp(a,b)
local t = {}
local i, len_a = 0
for w in (a..'/'):gmatch('(.-)/') do
i = i + 1
if w:sub(1,1) == ':' then
t[ -i ] = w:sub(2)
else
t[ i ] = w
end
end
len_a = i
i = 0
local ans = {}
for w in (b..'/'):gmatch('(.-)/') do
i = i + 1
if t[ i ] and t[ i ] ~= w then
return {}
elseif t[ -i ] then
ans[ t[ -i ] ] = w
end
end
if len_a ~= i then return {} end
return ans
end
s1 = '/foo/:bar/oof/:rab'
s2 = '/foo/lua/oof/rocks'
for k,v in pairs(comp(s1,s2)) do print(k,v) end
Another solution could be:
s1 = '/foo/:bar/oof/:rab'
s2 = '/foo/lua/oof/rocks'
pattern = "/([^/]+)"
function getStrngTable(_strng,_pattern)
local t = {}
for val in string.gmatch(_strng,_pattern) do
table.insert(t,val)
end
return t
end
local r = {}
t1 = getStrngTable(s1,pattern)
t2 = getStrngTable(s2,pattern)
for k = 1,#t1 do
if (t1[k] == t2[k]) then
r[t1[k + 1]:match(":(.+)")] = t2[k + 1]
end
end
The Table r will have the required result
The solution below, which is some what cleaner, will also give the same result:
s1 = '/foo/:bar/oof/:rab'
s2 = '/foo/lua/oof/rocks'
pattern = "/:?([^/]+)"
function getStrng(_strng,_pattern)
local t = {}
for val in string.gmatch(_strng,_pattern) do
table.insert(t,val)
end
return t
end
local r = {}
t1 = getStrng(s1,pattern)
t2 = getStrng(s2,pattern)
for k = 1,#t1 do
if (t1[k] == t2[k]) then
r[t1[k + 1]] = t2[k + 1]
end
end
Is there a more efficient way to execute the following jquery script? I need to access the 4 individual variables once the script has run, which I will then send to my database using ajax
var column_1 = $('#column-1').sortable("toArray");
for ( var i = 0, n = column_1.length; i < n; i++ ) {
var v = $('#' + column_1[i] ).find('.inner').is(':visible');
column_1[i] = column_1[i] + ":" + v;
}
var column_2 = $('#column-2').sortable("toArray");
for ( var i = 0, n = column_2.length; i < n; i++ ) {
var v = $('#' + column_2[i] ).find('.inner').is(':visible');
column_2[i] = column_2[i] + ":" + v;
}
var column_3 = $('#column-3').sortable("toArray");
for ( var i = 0, n = column_3.length; i < n; i++ ) {
var v = $('#' + column_3[i] ).find('.inner').is(':visible');
column_3[i] = column_3[i] + ":" + v;
}
var column_4 = $('#column-4').sortable("toArray");
for ( var i = 0, n = column_4.length; i < n; i++ ) {
var v = $('#' + column_4[i] ).find('.inner').is(':visible');
column_4[i] = column_4[i] + ":" + v;
}
This code has not been tested. But should work fine, does what you need it to do. ^^
function x ()
{
var columns = new Array();
columns.push({
column_1 : $('#column-1').sortable("toArray"),
column_2 : $('#column-2').sortable("toArray"),
column_3 : $('#column-3').sortable("toArray"),
column_4 : $('#column-4').sortable("toArray")
});
$.each(columns, function (key, item)
{
SaveToDatabase(item);
});
}
function SaveToDatabase (yourArray)
{
$.each(yourArray, function (key, item) {
var v = $('#' + item).find('.inner').is(':visible');
item = item + ":" + v;
});
}